Analisis Intensitas Modal, Biaya Utang, Dan Komisaris Independen Pada Agresivitas Pajak - Arianti, Baiq Fitri; Majidi, Lalu Muhammad Syahril (Universitas Gorontalo, 2023)
The study aims to test and analyze the effect of capital intensity, debt costs, and independent commissioners as independent variables, on Tax Aggressiveness as dependent variables. This research approach uses quantitative approaches with descriptive methods. The population of 163 manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 - 2020. The number of samples in this study amounted to 13 companies with purposive sampling methods, data that was successfully processed as many as 65 annual financial statement data. Statistical methods for data analysis using the eviews 10 application. The results of the panel's regression analysis test proved that partially, for capital intensity variables had a positive and significant effect on tax aggressiveness, the debt cost variable had a positive and insignificant effect on tax aggressiveness, while the independent commissioner variable had a negative and insignificant effect on tax aggressiveness.